x - 2
Wiki User
∙ 2010-05-13 15:44:30(2x - 3)(2x - 3)
4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2
x2 + 12x + 36 = 0(x + 6) (x + 6) = 0x+ 6=0 ;x + 6 = 0x = -6 ; x = -6
This doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-17 plus or minus the square root of -671) divided by 12x = -1.4166 + 2.158638974498103ix = -1.4166 - 2.158638974498103iwhere i is the square root of negative one.
If you mean: 4x squared+12x+9 then it is (2x+3)(2x+3)
4x + 20
2(x - 3)(x - 3)
That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3x = 0.07868932583326327x = -1.4120226591665965
(12x2 + 18) / (3x2 + 6) = (4x2 + 6) / (x2 + 2)
8x squared
With the help of the quadratic equation formula
2(2x-11)(3x+5)
2x(x−6)(x+1)
It is x^2 + 12x or x(x + 12).
4x2+12x = 4x(x+3) when factored
x(x + 3)(x - 4)
12x and then the squared. (the little two)